1963
DOI: 10.2170/jjphysiol.13.138
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Sympathetic Activity by Stimulation of Limbic System

Abstract: The concept of inhibition has been widely accepted in the study of the somatomotor function and the mechanism of inhibition has been extensively investigated(ECCLES,1961).However,the concept of inhibition has not been universely employed in the study of autonomic effects of brain stimulation. Effects were in most cases described as sympathetic or parasympathetic(HESS, 1936,RANSON and MAGOUN,1939 and KUROTSU et al.1958). Evidence of central inhibition of autonomic functions was recently pro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 3 publications
2
13
0
Order By: Relevance
“…lA and IB). This is in agreement with the work of Yokota et al (1963). The best evidence of HR deceleration without GSR was obtained with the point of stimulation in the area of the columns of the fornix.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…lA and IB). This is in agreement with the work of Yokota et al (1963). The best evidence of HR deceleration without GSR was obtained with the point of stimulation in the area of the columns of the fornix.…”
Section: Discussionsupporting
confidence: 91%
“…Yokota et al (1963) reported that inhibition of responses of skin potential and depression of blood pressure could be obtained by stimulation of the hippocampus and fornix. The depression elicited by the stimulation of these two structures did not disappear through atropinization, suggesting the existence of inhibition of vasomotor and sudomotor sympathetic activities.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothalamus, which is responsible for ANS activity, plays a major role in eliciting ipsilateral EDA under the direct influence of limbic structures [3]. These influences appear to stem from antagonistic actions of the amygdala (excitatory) and hippocampus (inhibitory) [4], [5]. Autonomic responses in the skin such as sweating, piloerection, and vasomotor changes can thus be elicited by various emotional states via the Papez circuit in the limbic system [6].…”
mentioning
confidence: 99%
“…An inhibitory center has been located in the ventromedial reticular formation in the midbrain, whereas the diencephalic part of the reticular formation excite EDA~Roy, Sequeira, & Delerm, 1993!. Excitatory influences from the hypothalamus and the amygdala have been reported from several animal preparations~Davison & Koss, 1975;Lang, Tuovinen, & Valleala, 1964;Yokota, Sato, & Fujimori, 1963!. Also, amygdala lesions in rhesus monkeys~Bagshaw, Pribram, 1965! andin humans compromise EDA~Bechara et al, 1995;LaBar, LeDoux, Spencer, & Phelps, 1995!. The role of hippocampus is unclear because findings from an-imal~Bagshaw et Edelberg, 1972;Yokota et al, 1963!…”
mentioning
confidence: 99%
“…Excitatory influences from the hypothalamus and the amygdala have been reported from several animal preparations~Davison & Koss, 1975;Lang, Tuovinen, & Valleala, 1964;Yokota, Sato, & Fujimori, 1963!. Also, amygdala lesions in rhesus monkeys~Bagshaw, Pribram, 1965! andin humans compromise EDA~Bechara et al, 1995;LaBar, LeDoux, Spencer, & Phelps, 1995!. The role of hippocampus is unclear because findings from an-imal~Bagshaw et Edelberg, 1972;Yokota et al, 1963! andhuman studies~Hazlett et al, 1993;Knight, 1996;Tranel & Hyman, 1990!…”
mentioning
confidence: 99%